Matrix Metalloproteinase-1 and -9 in Human Placenta during Spontaneous Vaginal Delivery and Caesarean Sectioning in Preterm Pregnancy - Sundrani, Deepali P.; Chavan-Gautam, Preeti M.; Pisal, Hemlata R.; Mehendale, Savita S.; Joshi, Sadhana R. (PLOS ONE, 2012)
Preterm birth is a major public health problem in terms of loss of life, long-term and short term disabilities worldwide. The process of parturition (both term and preterm) involves intensive remodelling of the extracellular matrix (ECM) in the placenta and fetal membranes by matrix metalloproteinases (MMPs). Our previous studies show reduced docosahexaenoic acid (DHA) in women delivering preterm. Further omega 3 fatty acids are reported to regulate MMP levels. This study was undertaken to examine the placental levels of MMPs and their association with placental DHA levels in women delivering preterm. The levels of MMP-1 and MMP-9 in 74 women delivering preterm (52 by spontaneous vaginal delivery and 22 by caesarean sectioning) and 75 women delivering at term (59 by spontaneous vaginal delivery and 16 by caesarean sectioning) were determined by enzyme-linked immunosorbent assay (ELISA) and their association with placental DHA was studied. Placental MMP-1 levels were higher (p<0.05) in women delivering preterm (both by spontaneous vaginal delivery and caesarean sectioning) as compared to those delivering at term. In contrast, placental MMP-9 levels in preterm pregnancies was higher (p<0.05) in women with spontaneous vaginal delivery while lower (p<0.05) in women delivering by caesarean sectioning. Low placental DHA was associated with higher placental MMP-9 levels. Our study suggests a differential effect of mode of delivery on the levels of MMPs from placenta. Further this study suggests a negative association of DHA and the levels of MMP-9 in human placenta although the mechanisms need further study.